Description Of Quality Learning Mathematics Of Students In Class Viewed From Emotional Intelligence In Class XI Transformation Materials In SMA 2 Majene - Djadir Djadir; Hamzah Upu; Hairunnisa Mahyuddin (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
Achievement of student learning outcomes and activities in learning is one of the things that can describe or is one of the benchmarks determining the quality of student learning. The emotional intelligence factor can affect the quality of learning. Therefore, the formulation of the problem in this study is how the description of the quality of mathematics learning of students is viewed from emotional intelligence on transformation material in SMA Negeri 2 Majene. The purpose of this study was to determine the description of the quality of mathematics learning of students in the classroom in terms of emotional intelligence on transformation material in SMA Negeri 2 Majene. This research is a type of qualitative research. The quality of student learning referred to in this study is the quality of student outcomes and activities. How to choose a subject that is by giving questionnaires to emotional intelligence to students then choose two students who have high emotional intelligence scores, two students with moderate emotional intelligence scores and two students with low emotional intelligence scores. The data collection method uses a combination of test, questionnaire and interview methods. Learning quality data obtained from quality test results and interviews of subject activities in the classroom. The results showed that the quality of the results of subjects with high emotional intelligence classified in the high and low categories, subjects with moderate emotional intelligence were both classified in the low category and subjects with low emotional intelligence classified in the medium and low categories, while for the quality of the process, the two subjects of emotional intelligence the first high and low emotional intelligence subject understands all indicators, whereas the second moderate emotional intelligence subject and the second low emotional intelligence subject do not meet all indicators